Using of Brainwriting to Write a Poem for First Semester Students of English Study ProgramMuhammadiyah University of Bengkulu - Arin Nurzalinda; Haniffa Putri; Agung Suhadi (UNIVED Press, 2018)
Poetry is a language that conveys something that is difficult to express and implies either expressed or implied. This aims as a material comparison between poetry writing techniques, both brainwriting techniques and ordinary writing techniques that are tested in class A at MuhammadiyahUniversity of bengkulu .This method used experimental methods. Systematic, logical, and meticulous research in controlling condition based on the results of observations of 24 respondents in class A the results of Brainwriting technique gives good impact to student to increase the accuracy of writing poetry more free and could devote more creative ideas in writing poetry. Keywords: brainwriting, technique, poetry, Muhammadiyah University of Bengkulu